Evaluation of the deleted in malignant brain tumor 1 protein expression and DNA methylation profile in rheumatoid arthritis patients - Khushboo Choudhury; Monika Gandhi; Uma Kumar; Sayan Chatterjee; Ram Singh Purty (Indian Journal of Rheumatology)
Background: Rheumatoid arthritis (RA) is a chronic, autoimmune disease that progressively leads to joint destruction and functional disability which eventually affects the quality of life of the people suffering from it. Deleted in malignant brain tumor 1 (DMBT1) role has been explored in progression of Sjögren's syndrome (SS) and other autoimmune diseases, whereas it has yet to be reported in RA. In this study, we have analyzed and evaluated the expression of DMBT1 protein and the dmbt1 genes' methylation status in healthy volunteers, RA, and SS patients. Methods: In the present investigation, the case–control study of 25 healthy volunteers and 17 RA- and 10 SS-confirmed patients was performed. Results: It was observed that the concentration of DMBT1 protein in saliva decreases in both the disease conditions compared to healthy volunteers, while methylation status of dmbt1 gene was low in both patient cohorts in comparison to the healthy controls. Conclusion: Results obtained from this study indicate that DMBT1 protein has the potential to qualify as a specific salivary biomarker as identified in RA and SS patients. DMBT1 protein can therefore be explored further as a noninvasive tool for diagnosis and prognosis.